(3TQM GdaQGFV GdSLGhfOjIs - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Gdedc GdYdGe hHYO aEfj deG aQZJ ef JUMjM GdeNJUQ GdeDda aj Yde GdaQGFV GdefShH Edi GdSLGhfOjs
(3BNQgG (B:s
(3ef Pdc jHbi GdSOS hddHfJ GdfUa hGdHGbj ddehdi dCf cdG efgeG dG jQK ef UGMHg eG hQK UGMHg efg abO GLJeY ddCe YTQhf hdcd efgeG SJhf hddehdi YTQI hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 133s
(3eYLe GdeDdajf (B1 / 148s
(3cTa GdXfhf (B2 / 12487s
(3TPQGJ GdPgH (B8 / 238s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs